Pengaruh kepuasan pelanggan, brand image, dan kepercayaan pelanggan terhadap loyalitas pelanggan pada membercard - Dwi Apriliani; Rizka Febila; Vicky F. Sanjaya; Nikmah Baqiyyatus Shalihah (Universitas Widya Mataram, 2020)
This research was conducted to determine the effect of satisfaction, brand image and trust on customer loyalty at member cards. This research method uses questionnaire data collection techniques with the respondent data of 100 people. The process of distributing questionnaires to respondents was carried out online and publicly. This type of research sampling technique used in this study is purposive sampling. Meanwhile, to test the data using validity and reliability tests. In testing the validity using the validity of the construction. This research was analyzed with the help of the smart PLS program. The results of the analysis obtained show that the customer satisfaction variable has a positive and significant effect on customer loyalty at member cards. Meanwhile, brand image has a negative and insignificant effect on customer loyalty to member cards and the variable customer trust also has a negative and insignificant effect on customer loyalty to member cards.